Development and Validation of Risk Stratification for Heart Failure After Acute Coronary Syndrome Based on Dynamic S100A8/A9 Levels - Jie Ma; Ke Ma; Jing Chen; Xinying Yang; Fei Gao; Hai Gao; Hui Zhang; Xin‐Liang Ma; Jie Du; Ping Li; Yulin Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The early assessment of heart failure (HF) risk in patients with acute coronary syndrome (ACS) can help reduce mortality. S100A8/A9 is not only rapidly released after myocardial ischemia, but is also involved in reperfusion injury, which is an important predictor of HF after ACS. We attempted to construct a reliable HF risk stratification tool for evaluating patients with ACS after reperfusion therapy based on S100A8/A9 dynamic changes. Methods and Results This prospective study included 3 independent cohorts of patients with ACS who received reperfusion therapy. The discovery cohort was divided into 2 subgroups: the longitudinal subgroup (n=264) with serum S100A8/A9 levels measured at admission and on days 1, 2, 3, and 4 postadmission, respectively, and the 2‐point subgroup (n=798) with S100A8/A9 levels measured at admission and on day 1 postadmission, respectively. Validation cohorts 1 (n=1399) and 2 (n=1183) both had S100A8/A9 levels measured on day 1 postadmission. HF events included in‐hospital HF events after the initial presentation and long‐term HF events after discharge. The median follow‐up for the discovery cohort, validation cohort 1, and validation cohort 2 was 4.2, 2.6, and 1.8 years, respectively. In the discovery cohort, S100A8/A9's predictive ability at day 1 surpassed other time points. Through the S100A8/A9‐guided risk stratification, patients deemed high risk (>7900 ng/mL) exhibited a higher 1‐year HF event rate (46% versus 2%, 38% versus 5%) than patients at low risk (<2100 ng/mL) in both validation cohorts. Among patients without left ventricular dysfunction after ACS, β‐blocker therapy correlated with reduced 1‐year HF events in intermediate‐to‐ high‐risk patients but not in low‐risk patients. Conclusions S100A8/A9 levels on day 1 accurately classified patients at varying risks of HF, serving as a robust tool for HF risk prediction and treatment guidance. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03752515.